Genomic analysis of familial pancreatic cancers and intraductal papillary mucinous neoplasms: A cross‐sectional study. Issue 5 (9th March 2022) - Abe, Kodai; Kitago, Minoru; Kosaki, Kenjiro; Yamada, Mamiko; Iwasaki, Eisuke; Kawasaki, Shintaro; Mizukami, Keijiro; Momozawa, Yukihide; Terao, Chikashi; Yagi, Hiroshi; Abe, Yuta; Hasegawa, Yasushi; et al.
Abstract: Environmental and genetic factors play a critical role in the pathogenesis of pancreatic cancer, which is likely to follow a multistep process that includes intraductal papillary mucinous neoplasm. The pathogenesis of familial pancreatic cancer has been reported; however, epidemiological characteristics and causative genes remain unclear. This study aimed to determine the relationship between the family history of pancreatic cancer and tumor malignancy and identify novel susceptible germline variants of pancreatic cancer. We performed an epidemiologic study at our institute on a cohort of 668 patients with intraductal papillary mucinous neoplasm and 242 with pancreatic cancer but without associated intraductal papillary mucinous neoplasm stratified by family history of pancreatic cancer. Whole‐exome sequencing was conducted for 10 patients from seven families with familial pancreatic cancer and intraductal papillary mucinous neoplasm. We found that patients who had intraductal papillary mucinous neoplasm with positive family history of pancreatic cancer within first‐degree relatives were more likely to develop malignancy in a shorter period than those without family history. Duplicate frameshift variants in TET2 c.3180dupG (p.Pro1061fs) and ASXL1 c.1934dupG (p.Gly646fs) in one family and POLN c.1194dupT (p.Glu399fs) in another were identified as pathogenic truncating germline variants which were previously recognised susceptibility genes. Moreover, PDIA2 c.1403C>T (p.Pro468Leu) and DPYSL4 c.926C>A (p.Pro309Gln) were shared in four and two patients, respectively. In particular, PDIA2 was identified as a novel candidate for one of the deleterious variants of familial pancreatic cancer. Abstract : Patients with intraductal papillary mucinous neoplasm with a family history of pancreatic cancer are more likely to develop malignancy in a shorter period than those without a family history. Of 18 patients with a strong family history of pancreatic cancer, three previously known susceptibility genes and one novel candidate gene were identified.